2018
DOI: 10.1088/1361-6595/aac070
|View full text |Cite
|
Sign up to set email alerts
|

Formation of stable inverse sheath in ion–ion plasma by strong negative ion emission

Abstract: The effect of strong charged particle emission on plasma-wall interactions is a classical, yet unresolved question in plasma physics. Previous studies on secondary electron emission have shown that with different emission coefficients, there are classical, space-charge-limited, and inverse sheaths. In this letter, we demonstrate that a stable ion-ion inverse sheath and ion-ion plasma are formed with strong surface emission of negative ions. The continuous space-chargelimited to inverse ion-ion sheath transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…1(a). Inverse sheath formation was recently shown to trigger temperature saturation in Hall thrusters [14], mode transitions in thermionic discharges [15], and ion-ion plasma formation in negative ion sources [13]. Inverse sheath theory also explains why emissive probes often float above the plasma potential [5].…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…1(a). Inverse sheath formation was recently shown to trigger temperature saturation in Hall thrusters [14], mode transitions in thermionic discharges [15], and ion-ion plasma formation in negative ion sources [13]. Inverse sheath theory also explains why emissive probes often float above the plasma potential [5].…”
mentioning
confidence: 98%
“…Recent works [12,13] find that SCL sheaths are destroyed by ion trapping in the virtual cathode (VC) and the equilibrium strongly emitting sheath must be inverse, see Fig. 1(a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies suggested that the SCL sheath cannot remain stable if cold ions are generated by charge exchange collisions in the sheath [11]. The emissive sheath is difficult to be directly accessed by conventional probe diagnostics due to its small size, so sheath theories are frequently validated against numerical simulations [12][13][14].…”
Section: Introductionmentioning
confidence: 99%